PREFERENSI GENERASI Z DALAM MEMBELI MINUMAN UKURAN VENTI DI STARBUCKS HARAPAN INDAH BEKASI BARAT - Kevin Gustian Yulius; Cherish Chriselina; Davin Darmadi; Rosianna Sianipar (Fakultas Pariwisata Universitas Pancasila, 2023)
Coffee is a famous Indonesia’s export commodity since the Dutch colonial era. The spread of coffee culture throughout the world was divided into waves, first, second and third. The second wave was marked by the existence of large businesses or cafes selling espresso-based drinks and spreading Italian culture, namely Starbucks. Famous for its complex pricing strategy that causing decoy effect on consumers. Consumers are presented with menu choices with asymmetrical prices, the larger the size of the product. This study seeks to analyze the factors that influence the decision to purchase Venti sized drinks, or the largest size at Starbucks Harapan Indah in Generation Z, which is Starbucks' biggest market. The results show that behavioral intention and price fairness have a significant influence on Generation Z's decision to buy Venti-sized drinks. However, price fairness influences it negatively, presumably because Generation Z does not consider price that much when purchasing something and does not yet have spending power. The decoy effect often has negative effects on the younger generation such as obesity and other diseases. Starbucks must pay attention to ethics in selling its products, and the government must supervise the sale of food or beverage products that contain high sugar. Keywords: Generation Z, Purchase Decision, Venti Sized Beverage